Dementia and cancer: a review of the literature and current practice. (June 2013) - Solomons, Luke; Solomons, Joyce; Gosney, Margot
Age is a risk factor for dementia, and also for most cancers. Surprisingly, rates of cancer appear to be lower in individuals with dementia and vice versa . Genetic mechanisms could underpin this inverse relationship and are outlined, but underdiagnosis must also be taken into account. Individuals with cancer and dementia pose unique challenges to healthcare professionals owing to the potential for impaired decision-making capacity, poor communication and difficulties following medication regimes. Mild cognitive impairment and 'chemo brain' should be differentiated from progressive neurodegeneration.